Hanuman Garhi Temple Complex - Temples of India Project Team (Jio Institute, 2024)
An overview of the Hanuman Garhi temple complex from the eastern side. Seen here (from left to right) are many Shiva temples, behind it is the Hanuman temple with a flag, the Kumbheshwar temple and the Nilkhanth Mahadev temple with Surya Kund in front of it. The Hanuman statue enshrined in the Hanuman temple dates to the eleventh century CE.